Depth Analysis for Sensitivity Pattern Section in the Electrical Resistivity using the 2D Computerized Modeling Method - Bery, Andy Anderson (Mete Oner, 2014)
This paper presents the analysis of depth of investigation factors which are (Zm/a) and (Zm/L). The medium depth of investigation (Zm) from the sensitivity pattern of different arrays influences the array selection which is good enough for planning infield surveys. In this paper, the average maximum for data level n value for inline dipole-dipole, pole-dipole and Wenner-Schlumberger for a good subsurface investigation is 6. Then, the spacing of current and potential electrode pair which is a value must be increased. The 2D sensitivity section using the computerized modeling method for each array is able to assist the user in choosing the appropriate array for a practical survey planning after carefully balancing factors such as the cost, investigation depth and resolution. Among the matters for array selection that should be considered are (1) the signal strength, (2) sensitivity of the array to horizontal and vertical changes in the resistivity pattern, (3) investigation depth and (4) horizontal data coverage. Beside than that, the use of appropriate constraint parameters and proper array selection will lead to a better processing and interpretation work in order get reliable and acceptable results. In additional, this paper introduces a new hybrid array called Andy-Bery array. In the application, this new hybrid array is successful and reliable in imaged the conductive block model with it’s actual dimension.